Aid for trade making it effective. (OECD, 2006)
This book sets out how much aid OECD countries are already providing towards trade-related activities in developing countries and reviews the effectiveness of existing programs. It argues that reinforcing mutual accountability at the local level, together with a global review mechanism, would enhance the impact of Aid for Trade.--Publisher's description.